2019
DOI: 10.31080/asor.2019.02.0100
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Forearm Circumference and Hand Length with Grip Strength in Healthy Young Adults

Abstract: Introduction: Grip strength measurement is used as an indicator for many hand and forearm related orthopaedic injuries as well as in neurological assessment. Aim: To find whether anthropometric measurements like hand length and forearm circumference have influence on hand grip strength of young healthy adults. Material and Methods: 198 healthy young adults were used for the study for data collection. Grip strength of both hands were done with hand held dynamometer. Anthropometric measurements of hand length an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…As a result of the study by Seethamma et al (14), it was found that grip strength was directly related to the anthropometric measurement of hand length and forearm circumference, and therefore grip strength was associated with hand length and forearm circumference regardless of age and gender. While we obtained similar results to Seethamma et al (14), contrary to the results of our study, Nefesoğlu et al (15) reported that grip strength was associated with forearm length, arm circumference, and wrist circumference. Contrary to our results, Narin et al (6) reported that grip and finger grip strength were higher in individuals with longer forearms and more circumference measurements.…”
Section: Discussionmentioning
confidence: 94%
“…As a result of the study by Seethamma et al (14), it was found that grip strength was directly related to the anthropometric measurement of hand length and forearm circumference, and therefore grip strength was associated with hand length and forearm circumference regardless of age and gender. While we obtained similar results to Seethamma et al (14), contrary to the results of our study, Nefesoğlu et al (15) reported that grip strength was associated with forearm length, arm circumference, and wrist circumference. Contrary to our results, Narin et al (6) reported that grip and finger grip strength were higher in individuals with longer forearms and more circumference measurements.…”
Section: Discussionmentioning
confidence: 94%
“…The results of this study did not show associations between physical performance tests and SMI. Although these tests have been considered reliable in examining musculoskeletal functions, a plausible explanation would be the fact that several studies have shown that the amount of muscle mass does not necessarily correspond to its functionality (Newman et al 2006, Loenneke 2019) and that there are other factors that can influence muscle strength: a diversity of neurophysiological processes beyond muscle size, such as neuronal adaptations to different load resistance training (Jenkins et al 2017), and the type of muscle fibers and body proportions, that could also have significant and independent effects on muscle strength (Enoka 1988, Schoenfeld et al 2019, Seethamma et al 2019. Our results are similar to those of a recent study aimed at comparing the associations of Body Mass Index (BMI) and SMI by BIA (among others) with the HGST, walking speed and SPPB of 428 elderly people aged 75 to 96 years at risk or suffering from sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Study Participants: Study participants (both male and female) who attended the different medical camps conducted by the doctor's community program for 3 months (January 2019 to April 2019), in Kerala were selected for the observational field study (Non-interventional) 14,15 . Study participants from age 12 to 70, with the willingness to participate, were recruited after getting verbal consent.…”
Section: Materials and Methods: Type Of Study: Diagnostic Accuracy St...mentioning
confidence: 99%
“…Those with any history of arm, forearm, wrist and fingers fracture, nerve injury, or surgical history of upper limb were excluded from the study 15 .…”
Section: Materials and Methods: Type Of Study: Diagnostic Accuracy St...mentioning
confidence: 99%
See 1 more Smart Citation